Cdk1-Dependent Phosphorylation of the APC-Cdc20 Regulates its Activation at Anaphase Onset in S. cerevisiae - Williams, Elizabeth C. (Université d'Ottawa / University of Ottawa, 2015)
The metaphase to anaphase transition of the cell cycle is triggered by activation of the anaphase promoting complex (APC) bound to its mitotic activator, Cdc20. The APC is a multisubunit E3 ubiquitin ligase that targets mitotic substrates for proteasomal degradation, including securin (Pds1 in S. cerevisiae), which allows for the separation of sister chromatids at anaphase onset. Activation of the APC is thought to be regulated by both Cdk1-dependent phosphorylation and the binding of Cdc20. We show that inhibition of Cdk1-dependent phosphorylation of the APC, by overexpression of the tyrosine kinase Wee1 (Swe1 in S. cerevisiae), stabilizes mitotic substrates, impairs sister chromatid separation and arrests cells in metaphase. Inhibition of Cdk1-dependent phosphorylation of the APC also inhibits ubiquitination activity in vitro. We further show that although Cdk1 phosphorylation of the subunits Cdc16, Cdc23 and Cdc27 is important for ubiquitination activity, Cdk1 likely phosphorylates additional subunits of the APC that contribute to maximal activity at the metaphase-anaphase transition. In contrast to previous reports, however, we find that this phosphorylation does not influence binding of the mitotic activator, Cdc20. Mitotic APC activity is also regulated by the spindle assembly checkpoint (SAC), which inhibits Cdc20-dependent activity in response to spindle damage or unattached kinetochores. We find that preventing Cdk1-dependent phosphorylation of the TPR subunits delays recovery from activation of the SAC. We also show that preventing this phosphorylation in combination with loss of the APC subunits Cdc26 and Mnd2 causes sensitivity to activation of the spindle assembly checkpoint. Overall, we argue that Cdk1-dependent phosphorylation is important for APCCdc20 activity at the metaphase-anaphase transition. In addition, our data suggests that this phosphorylation may also be important for normal SAC function, defining a novel function for Cdk1 phosphorylation of the APC.